2007
DOI: 10.1515/epoly.2007.7.1.1176
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics modeling of the reaction for an Epoxy/PMMA/MMT ternary system

Abstract: Abstract:The effect of thermoplastic PMMA and clay Cloisite 30B addition on the cure kinetics of an epoxy/amine thermosetting system was investigated using differential scanning calorimetry (DSC) and modelled using a single kinetic model. For obtaining a good agreement between the experimental results and theoretical modeling, it was necessary to separate the ternary system in two formulations: matrix/PMMA and matrix/clay systems. It appeared that the addition of PMMA delays the reaction up to the phase separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In most cases, stiffness was the result of balancing the ratio of soft and hard fillers, and toughness was improved via multiple cracks and crack bifurcation mechanisms. Thermoplastics undergoing RIPS as PMMA were also used, leading to significant improvements in toughness 18, 19. Not only rubbers but also TPs can have a toughening effect at room temperature, mainly by crack bridging and crack pinning mechanisms3, 4…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, stiffness was the result of balancing the ratio of soft and hard fillers, and toughness was improved via multiple cracks and crack bifurcation mechanisms. Thermoplastics undergoing RIPS as PMMA were also used, leading to significant improvements in toughness 18, 19. Not only rubbers but also TPs can have a toughening effect at room temperature, mainly by crack bridging and crack pinning mechanisms3, 4…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that melt‐blended ternary epoxy composites exhibited higher fracture toughness parameter (K C ) values in comparison with those prepared by ultrasonic mixing. The same authors studied the addition of thermoplastic (PMMA) and montmorillonite (Cloisite 30B) modifiers on the cure kinetics of an epoxy resin cured with amine using differential scanning calorimetry (DSC) . It was confirmed that the addition of PMMA delays the reaction up to the phase separation phenomenon due to a dilution effect of the reactive species.…”
Section: Introductionmentioning
confidence: 97%
“…The brittle fracture and low impact strength are the disadvantages of epoxies. The addition of initially soluble TP is consciously used to improve the toughness of epoxy materials [10][11][12][13][14][15][16][17][18][19][20][21]. The cited references comment DGEBA modified ER having weight average molecular mass, M w , within the range 340-390 kg kmol À1 .…”
Section: Introductionmentioning
confidence: 99%
“…These groups are capable of interacting with the end groups of PET through hydrogen bonding. On the other hand, DGEBA are good solvents of other TPs having different chemical formulas, e.g., polystyrene, PS [13], polymethyl methacrylate, PMMA [14], polyvinyl methylether, PVME [15], polyether imide, PEI [16], polyether sulphone PES [17] and others, see [10][11][12] and references herein. It can be assumed that hydrogen bonding is the probable reason that causes solubility of TP in DGEBA.…”
Section: Introductionmentioning
confidence: 99%